Deflection and Stress Analysis of Sandwich Plates Under Uniformly Distributed Load - Parveen, Saniya; Bose, Malobika (Journal of Research in Science and Engineering, 2026)
The deflection and stress values of sandwich plate with uniformly distributed load (UDL) are investigated. The sandwich structure is modeled using the First order shear deformation theory for the mathematical purpose. The analysis of deflection and stress values is done in ANSYS 18.0 software. Lastly, the influences of structural parameters (Face to core thickness ratio, aspect ratio, thickness ratio, boundary conditions) the deflection and stress values are obtained, and for subsequent conclusions discuss accordingly.